Hubungan Keaktifan Ibu dalam Posyandu dengan Status Gizi Balita di Desa Sei Rotan - Dian Firza; Delfriana Ayu A (Jurnal Kesehatan Masyarakat Indonesia, 2022)
Background: Malnutrition can be detected early by identifying the growth and development of children in Posyandu. In North Sumatra, the prevalence of malnutrition fluctuated especially in 2016 by 10.08%, in 2017 by 13.10%, and in 2018 to 14.30%. Objective: To determine the relationship between the activeness of mothers in posyandu with the nutritional status of children under five in Sei Rotan Village. Methods: The type of research in this study is an analytical survey research with a cross sectional design. The number of samples as many as 41 respondents with a simple random sampling technique. Result: There is a relationship between the activity of mothers in the posyandu with the nutritional status of children under five, which is obtained from the results of the P-Value = 0.003 with a significant level (p<α). It is hoped that the results of this study can be used as a source of information about the activities of posyandu mothers in nutritional status. Conclusion: There are 14 mothers under five (34.1%) who are active in posyandu and 27 mothers of children under five (65.9%) who are not active in posyandu. There are 20 toddlers (48.8%) with underweight, 9 toddlers (22.0%) having a normal diet, 10 toddlers (24.2%) with an increased risk of obesity and 2 toddlers (4.9%) with obesity